2020
DOI: 10.18415/ijmmu.v7i7.1727
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis: Factors Affecting Students’ Reading Interest in Indonesia

Abstract: The increasingly intense industrial era competition needs to be balanced with the ability to process and utilize various sources of information. One of the efforts that needs to be done to obtain this information is indeed through reading. However, the data shows that the interest in reading especially students in Indonesia is still very low. Many factors affect. One of them is the technology that makes students distracted by using various media only for entertainment and social media. Based on this, the purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…This suggests that factors other than the development of library facilities and infrastructure can also influence the reading interests of Net Generation youth. Therefore, further research is needed to identify other factors that can affect the reading interest of Net Generation youth and to develop appropriate strategies (Pitoyo, 2020) (Weaver & Mutti, 2021) (Khongtim, 2021) (Akhtar & Ather Khan, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that factors other than the development of library facilities and infrastructure can also influence the reading interests of Net Generation youth. Therefore, further research is needed to identify other factors that can affect the reading interest of Net Generation youth and to develop appropriate strategies (Pitoyo, 2020) (Weaver & Mutti, 2021) (Khongtim, 2021) (Akhtar & Ather Khan, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Tujuan dari meningkatkan minat baca ini guna menghasilkan masyarakat yang gemar membaca, masyarakat pembelajar dalam rangka mencerdaskan kehidupan bangsa yang diisyarati dengan terciptanya sumber daya manusia yang bermutu selaku media pembangunan nasional menuju masyarakat madani. Tidak hanya itu dengan membaca membuka pengetahuan, menambahkan wawasan serta keahlian dan menambah kreativitas akibatnya anak lebih energik untuk tetap membaca (Pitoyo, 2020). Oleh sebab itu, di dedikasi ini harus mampu mempublikasikan perilaku membaca yang positif melalui membaca.…”
Section: Pendahuluanunclassified
“…Ideally, with a variety of media, it gives interest to information. Pitoyo (2020) suggested that reading interest is influenced by literacy activities, technology, and library facilities. Everyone needs to be interested in reading because the success, progress of the nation, and the quality of human resources can be improved through reading (Yukaristia, 2019).…”
Section: Introductionmentioning
confidence: 99%